THE EFFECTIVENESS OF COACHES’ LEADERSHIP COMPETENCE IN PROMOTING SOCIAL INTERACTION AMONG PLAYERS WITH SPECIAL NEEDS - Yasin, Mustafa Ismail; Mohammed, Jasim Ali (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Sports activities for people with special needs play a prominent role among the means that contribute to fostering social interaction among team members and within the community, as they create a social environment that facilitates cooperation, communication, acceptance, and the exchange of experiences between team members and the coach. Objectives. The study aimed to identify the effectiveness of coaches’ leadership competence and its role in enhancing the social interaction of athletes with special needs, to determine the level of leadership they exhibit from their athletes’ perspective, to identify their level of social interaction, and to determine whether there is a correlation between the two variables. Method. To achieve this, the researchers conducted their study on a sample of 60 athletes with special needs at the Paralympic Committee’s office in Maysan Governorate, who represent the total research population. Results. The researchers concluded that coaches of athletes with special needs possess a high level of leadership competence from the athletes’ perspective, which reflects their ability to plan effectively, make appropriate decisions, communicate effectively, and motivate athletes to participate in sports activities. Athletes with special needs exhibit a moderate to high level of social interaction, indicating that this group has the ability to interact with others, form social relationships, and communicate with their peers. Conclusion. The researchers also recommend the need to work on strengthening and developing the role of coaches and enhancing their leadership skills through training courses and workshops focused on planning, decision-making, communication, and motivation, thereby contributing to raising the team’s overall performance level. It is necessary to implement activities and programs that contribute to creating a social environment that encourages communication among team members and the community at large, such as teamwork, friendly competitions, and joint activities outside of training hours, to reduce the gap between leadership competence and social interaction.